Are student exchange programs worth it? - Dolores Messer; Stefan C. Wolter (Institute for the Study of Labor (IZA), 2005)
The number of university students participating in exchange programs has risen sharply over the last decade, but a survey of Swiss university graduates (class of 1999 and 2001) shows that participation in student exchange programs significantly prolongs the period of time spent studying at university. Given this fact, the advantages of exchange programs for students need to be identified. Analyses show that student exchange programs are associated with higher starting salaries and an increased likelihood of opting for postgraduate study - but only if all exchange semesters are factored in, not just those accredited by the university of matriculation. Using instrumental variable estimations (IV), however, shows that the cited outcomes are not causally related to participation in exchange programs. Therefore the big question is: Where's the benefit that justifies having to study for almost a whole year longer?
Keywords: I23; J24; J31; J44; 330; exchange semester; ERASMUS; graduate survey; instrumental variables; Switzerland